Olig2 overexpression accelerates the differentiation of mouse embryonic stem cells into oligodendrocyte progenitor cells in vitro. (9th September 2014) - Yao, Ruiqin; Wang, Bei; Ren, Chuanlu; Qu, Xuebin; Luo, Mengjiao; Zhang, Qiang; Wang, Huiping; Dong, Fuxing; Wu, Xiuxiang; Yang, Lihua; Yu, Hongli
<x xml:space="preserve">Abstract</x> Oligodendrocyte progenitor cells (OPCs) transplantation is receiving considerable attention in the field of regenerative medicine therapy for demyelinating diseases. Although embryonic stem cells (ESCs) have been successfully induced to differentiate into OPCs with cytokines cocktails in vitro, the regulatory roles of many key transcription factors in this process are not clear. Here, we introduced oligodendrocyte lineage transcription factor 2 (Olig2), a basic helix‐loop‐helix transcription factor, into mouse embryonic stem cells (mESCs) to investigate its effects on the differentiation of mESCs into OPCs. The results showed that Olig2 overexpression alone did not affect pluripotency of mESCs, but in the stimulation of differentiating cocktails, Olig2 accelerated mESCs to differentiate into OPCs, shortening the induction time span from normal 21 days to 11 days. Further study demonstrated the Olig2‐mESCs derived OPCs were able to differentiate into C‐type natriuretic peptid (CNP) and Myelin Basic Protein (MBP) positive mature oligodendrocytes (OLs) in vitro, suggesting these induced OPCs might be favorable for myelin regeneration in vivo.